Thoracic radiation in combination with erlotinib—results from a phase 2 randomized trial - Nymoen, Hanne Marte; Alver, Tine Norman; Horndalsveen, Henrik; Eide, Hanne Astrid; Bjaanæs, Maria Moksnes; Brustugun, Odd Terje; Grønberg, Bjørn Henning; Haakensen, Vilde Drageset; Helland, Åslaug (Frontiers in Oncology, 2024)
Radiotherapy can be used to reduce symptoms and maintain open airways for patients with non-small cell lung cancer when systemic treatment is not sufficient. For some patients, tumor control is not achieved due to radio-resistance. Concurrent inhibition of epidermal growth factor receptors has been proposed as a strategy to overcome radio-resistance but may increase toxicity. We performed a randomized trial to assess the efficacy, tolerance and quality of life of concurrent erlotinib and palliative thoracic radiotherapy for patients with advanced non-small cell lung cancer.Patients were randomized 1:1 to radiotherapy alone (arm A) or in combination with erlotinib (arm B). A CT scan at baseline and one at 4 -12 weeks after inclusion was used to evaluate treatment response. Adverse events were registered during treatment and the subsequent 30 days. Health-related quality of life questionnaires were completed by the patients at baseline, week 2, week 6 and week 20.A total of 114 patients were included. Of the 74 patients with CT scans available for evaluation of treatment effect, there were no significant differences in tumor size reduction between the two groups: median 14.5% reduction in the control arm A and 17.0% in the erlotinib arm B (p=0.68). Overall survival was not significantly different between the two treatment arms: 7.0 and 7.8 months in arm A and arm B, respectively (log-rank p=0.32). There was no significant increase in adverse events in the experimental arm, other than what is expected from erlotinib treatment alone. Overall, patients reported similar quality of life in both treatment arms.Concurrent erlotinib and palliative thoracic radiotherapy for patients with advanced non-small cell lung cancer was well tolerated but did not improve the efficacy of the radiotherapy.